Exploring microbial community diversity of mango leaf compost (Current Horticulture, 2024)
A microbial consortium of 6 bacterial (Lactobacillus sp., Acetobacter sp., Saccharomyces sp., Bacillus sp., Pseudomonas sp. and Microascus sp.) and 5 fungal isolates (Aspergillus niger, A. oryzae, Fusarium solani, Trichoderma viridae and Penicillium citrinum), isolated from degrading organic substrates and having high degradative enzyme activities, was used for composting of mango leaves. It took one month for complete composting. The ready compost was subjected to physico-chemical, microbial and metagenomic analyses. The culturable bacterial and fungal isolates were purified and maintained on nutrient agar and potato dextrose agar slants and identified using 16S rDNA and ITS region sequencing. Molecular identification of cultured bacteria reflected the dominance of Bacillus subtilis along with Bacillus sp. and Microbacterium sp. The fungal isolates included Trichoderma sp,. Aspergillus niger, Acremonium sclerotigenum, Alternaria sp., Trichoderma sp. and Geotrichum candidum. Metagenomic analysis of mango (Mangifera indica) leaf compost resulted in 22842 number of total operational taxonomic units (OTU). At phylum level, 35% and 24% of OTUs were assigned with Ascomycota and Basidiomycota respectively. Rest belonged to unidentified phyla. At class level, 25% and 24% of OTUs were assigned with Sordariomycetes and Agaricomycetes, respectively. At genus level, 12% and 10% of OTUs were assigned with Coprinus and Zopfiella, respectively. The study indicated that despite the addition of microbial consortium, during the process of composting, microbes are coming from the environment which are helping in composting process.
Keywords: Mango leaf; Compost; Metagenome; Bacteria; Fungi; Operational taxonomic units